Renal Nutrition-Where It Has Been and Where It Is Going - Joel D. Kopple; Maryam Ekramzadeh (MDPI AG, 2022)
This paper is a synopsis of an invited lecture entitled, The Future of Renal Nutrition, that was presented at the Japanese Society of Dialysis Therapy, July 2022. The purpose of this presentation is to suggest some of the advances in the field of renal nutrition that the authors think are likely to occur during the next several years. There will be continued development of methods for precisely diagnosing and classifying protein-energy wasting and developing methods to treat this disorder. Why weight loss commonly occurs when the GFR decreases to about 30-35 mL/min/1.73 m2 and why substantial weight loss (>5%/year) is associated with increased mortality will be investigated. Clinical consequences of the interactions between gut microbiota, nutrient intake and other environmental influences will continue to be examined. The clinical value of diets high in fruits and vegetables or other plants for chronic kidney disease (CKD) patients will continue to be studied. Our knowledge of how different diets and medicines affect intestinal absorption, metabolism and excretion of nutrients will expand. Precision medicine will be extended to precision nutrition. There will be more focus on the effects of nutritional disorders and dietary treatment on the emotional status and quality of life of people with kidney disease and their families. Nutritional centers that provide centralized nutritional assessment and dietary counselling for CKD patients may develop in more urban centers. More clinical trials will be conducted to test whether nutritional management improves clinical outcomes in people with kidney disease. It is hoped that the foregoing comments will encourage more research on these topics.